Fake News in Digital Cultures : Technology, Populism and Digital Misinformation - Cover, Rob; Haw, Ashleigh; Thompson, Jay Daniel (Emerald Publishing Limited, 2022)
Fake News in Digital Cultures presents a new approach to understanding disinformation and misinformation in contemporary digital communication, arguing that fake news is not an alien phenomenon undertaken by bad actors, but a logical outcome of contemporary digital and popular culture.